Association Between Diabetes Risk Reduction Diet and Lung Cancer Risk in 98,159 Participants: Results From a Prospective Study - Zhang, Yin; Zhong, Guochao; Zhu, Min; Chen, Ling; Wan, Huajing; Luo, Fengming (Frontiers in Oncology, 2022)
Purpose: To evaluate the association between diabetes risk reduction diet (DRRD) score and the risk of lung cancer in a large population. Methods: Data of participants in this study were collected from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated in Cox proportional hazards regression for the association of DRRD score and lung cancer incidence in all included participants. Prespecified subgroup analyses were performed to evaluate whether the observed association was modified by age, sex, BMI, race/ethnicity, family history of lung cancer, smoking status and history of diabetes. Results: A total of 98,159 participants were included in this study. The mean (SD) age of the study participants cohort at baseline was 65.5(5.73) years old. The mean (SD) follow up time was 8.83 (1.96) years. The mean (SD) score of DRRD was 26.82 (5.19), ranged from 20.47(2.3) to 33.65(2.42) from the lowest quartile to the highest quartile of DRRD score, inferring the possibility of highest though the lowest risk of type 2 diabetes. The calculated HRs showed there was a trend that higher quartile indicated lower risk of lung cancer after adjusted for covariates (HRQ4vsQ1: 0.85; 95% CI:0.73,0.98; p for trend =0.036). The inverse trend between higher DRRD score and squamous cell carcinoma was more evident (HRQ4vsQ1: 0.50; 95% CI:0.34,0.73; p for trend =0.002). The inverse association between DRRD score and the incidence of lung cancer was more pronounced in participants who had a clear family history of lung cancer (p for interaction=0.016). Conclusion: A protective association between DRRD score and risk of lung cancer is obtained. People are encouraged to adhere to higher DRRD score in daily diet. Further studies should be conducted to confirm the result and explore the mechanism.